Pengembangan Media “MEB” dalam Menumbuhkan Rasa Nasionalis pada Pembelajaran Matematika SD - Kunti Dian Ayu Afiani; Meirza Nanda Faradita (Jurnal Bidang Pendidikan Dasar, 2021)
This research is a research and development that aims to produce a valid and effective MEB (Monopoly Education Book) media in fostering a nationalist sense of the Indonesian nation in learning mathematics. The research subjects were fourth grade students of SDN Wonokromo 1 Surabaya. The development of this media in its stages is limited to the mass production stage. Where the validity has been validated against three validators. The results of the research from the three validation results that have been given can be average and it is concluded that the MEB (Monopoly Education Book) media that has been developed gets a score of 86% where the score is included in the "Very Good" criteria. And the MEB (Monopoly Education Book) media is effective as evidenced by the completeness of the classical learning outcomes of students reaching 76%. Thus the learning media MEB (Monopoly Education Book) can be said to be valid and effective.